Origin, Domestication, Dissemination and Genetic Diversity of Coconut: DNA information - Lalith Perera (International Coconut Community, 2001)
Information on origin, dissemination and levels and distribution of genetic diversity in coconuts will allow plant breeders and conservationists to select better breeding materials and formulate appropriate conservation strategies. PCR-based DNA profiling of coconut palms from Sri Lanka was initially conducted using both Amplified Fragment Length Polymorphism (AFLPs) and Microsatellites (SSRs). Thirty-nine microsatellite primers specific to coconut were developed by small insert genomic library construction. Eighteen of those primers were used to analyze the same set of Sri Lankan coconut materials. Overall, the results generated by both AFLPs and SSRs were in agreement. Most diversity was found in the tall variety (Typica) (0.92 and 0.62 for AFLPs and SSRs, respectively) rather than the intermediate (Aurantiaca) and dwarf (Nana) varieties (0.82 and 0.25 for AFLPs and SSRs, respectively). A hierarchical analysis of molecular variance (AMOVA) based on AFLP data was used to quantify and partition levels of variability between and within form components. This revealed that for the inbreeding dwarf and intermediate forms most variation was observed between rather than within forms. In contrast, the out-breeding tall forms exhibited as much variation within as between forms.